Generation of Urine Cell-Derived Non-integrative Human iPSCs and iNSCs: A Step-by-Step Optimized Protocol - Cheng, Lin; Lei, Qiannan; Yin, Chen; Wang, Hui-Yun; Jin, Kangxin; Xiang, Mengqing (Frontiers in Molecular Neuroscience, 2017)
Objective: Establishing a practical procedure to generate induced pluripotent stem cells (iPSCs) and induced neural stem cells (iNSCs) from human urine cells (UCs). In this report, we optimized a non-integrative protocol to generate patient-specific iPSC and iNSC lines with high reprogramming efficiency. Methods: UCs were electroporated with the pEP4-EO2S-ET2K and pEP4-M2L plasmids containing the OCT4, SOX2, KLF4, SV40LT, c-MYC, and LIN28 genes, and then cultured with N2B27 medium plus 4 small molecule compounds (A83-01, PD0325901, Thiazovivin, and CHIR99021). When iPSC or iNSC clones emerged, the medium was replaced with mTeSR1 or neural growth medium. Morphological changes were seen at day 4-7. After day 10, the clones were picked up when the clone diameter exceeded 1 mm. Results: iPSCs and iNSCs were successfully derived from UCs with up to 80 clones/well. These iPSCs and iNSCs showed typical hESC or NSC morphology and were self-renewable. The iPSCs had pluripotency to differentiate into the three germinal layers and displayed high levels of expression of pluripotency markers SOX2, NANOG, OCT4, SSEA-4, TRA-1-60, TRA-1-81, and alkaline phosphatase (AP). They maintained normal karyotype and had no transgene expression or genomic integration. The iNSCs were positive for NSC markers NESTIN, PAX6, SOX2 and OLIG2. Conclusion: The optimized protocol is an easy and fast procedure to yield both iPSC and iNSC lines from a convenient source of human urine in a single experiment.